POEMS syndrome: a case report - Gutiérrez Araujo, Vianca (2022)
POEMS syndrome is a disease of unknown pathogenesis. The acronym stands for the disease’s main clinical manifestations: polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin disorders. Recent studies suggest the association of genetic mutations with immunoglobulin λ. We report the case of a 56-year-old male patient with a 10-month clinical picture, whose initial signs and symptoms were lower limb edema and hypertrichosis, followed by gastrointestinal symptoms, inguinal lymphadenopathy and lower limb paresthesia. We emphasize the importance of this clinical case, given the limited reports of POEMS syndrome at the national level and no reported cases in the department of La Libertad, and the long time it takes to diagnose such disease.